2013
DOI: 10.1161/circulationaha.112.000711
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Reduces Angiographic Restenosis After Endovascular Therapy for Femoropopliteal Lesions in the Sufficient Treatment of Peripheral Intervention by Cilostazol Study

Abstract: Background-It remains unclear whether cilostazol, which has been shown to improve the clinical outcomes of endovascular therapy for femoropopliteal lesions, also reduces angiographic restenosis. Methods and Results-The Sufficient Treatment of Peripheral Intervention by Cilostazol (STOP-IC) study investigated whether cilostazol reduces the 12-month angiographic restenosis rate after percutaneous transluminal angioplasty with provisional nitinol stenting for femoropopliteal lesions. Two hundred patients with fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 25 publications
3
80
0
2
Order By: Relevance
“…A smaller study in 2009 15 also found similar results with restenosis rates (43% vs 70.3%). These findings were validated in a larger multicentre study in 2013 with 200 patients 16 that demonstrated an angiographic restenosis rate at 12 months of 20% in cilostazol group versus 49% in the non-cilostazol group.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…A smaller study in 2009 15 also found similar results with restenosis rates (43% vs 70.3%). These findings were validated in a larger multicentre study in 2013 with 200 patients 16 that demonstrated an angiographic restenosis rate at 12 months of 20% in cilostazol group versus 49% in the non-cilostazol group.…”
Section: Resultsmentioning
confidence: 55%
“…The main characteristics of individual studies can be found in Table 2 illustrates baseline characteristics of populations in the individual studies. All baseline variables including stenting ratio were similar in all studies with the exception of preprocedural Ankle Brachial Index (ABI) in Iida et al 16 ; despite both groups having the ABI on the moderate disease range it was higher on the cilostazol group (0.71 vs 0.66).…”
Section: Resultsmentioning
confidence: 66%
“…Concerns over the high risk of cardiovascular (CV) mortality in patients with PAD have prompted studies evaluating the effect of cilostazol on CV outcomes. Importantly, recent evidence from randomized trials has established the benefits of cilostazol to prevent restenosis and reocclusion after peripheral endovascular procedures [24,25]. Further, cilostazol has proven efficacy and safety in reducing target lesion revascularization in those patients receiving hemodialysis after procedures for PAD [26][27][28].…”
Section: Peripheral Arterial Diseasementioning
confidence: 99%
“…The most recent randomized controlled trial published in this area is the Sufficient Treatment of Peripheral Intervention by Cilostazol (STOP-IC) study [25]. This multicenter, open-label, prospective study randomized 200 Japanese patients with symptomatic PAD to receive aspirin 100 mg daily plus cilostazol 200 mg daily compared to aspirin alone to determine the 12-month effect of cilostazol on restenosis after EVT with provisional stenting for FP lesions.…”
Section: Reducing Restenosis After Endovascular Proceduresmentioning
confidence: 99%
See 1 more Smart Citation